Nanoassembly routes stimulate conflicting antibody quantity and quality for transmission-blocking malaria vaccines - Darren B. Leneghan (Nature Portfolio, 2017)
Abstract Vaccine development efforts have recently focused on enabling strong immune responses to poorly immunogenic antigens, via display on multimerisation scaffolds or virus like particles (VLPs). Typically such studies demonstrate improved antibody titer comparing monomeric and nano-arrayed antigen. There are many such studies and scaffold technologies, but minimal side-by-side evaluation of platforms for both the amount and efficacy of antibodies induced. Here we present direct comparison of three leading platforms displaying the promising malaria transmission-blocking vaccine (TBV) target Pfs25. These platforms encompass the three important routes to antigen-scaffold linkage: genetic fusion, chemical cross-linking and plug-and-display SpyTag/SpyCatcher conjugation. We demonstrate that chemically-conjugated Qβ VLPs elicited the highest quantity of antibodies, while SpyCatcher-AP205-VLPs elicited the highest quality anti-Pfs25 antibodies for transmission blocking upon mosquito feeding. These quantative and qualitative features will guide future nanoassembly optimisation, as well as the development of the new generation of malaria vaccines targeting transmission.